Necesidad de equilibrio entre protección de la inversión extranjera y protección de la salud pública: a propósito de la pandemia de la covid-19 - Carbajal Valenzuela, Christian (2020)
International Investment Law, and Investment Arbitration in particular, are at a stage of change and challenge, which will be accelerated as a result of disputes that will arise as a result of the COVID-19 pandemic. In recent years, both, Investment Treaties and investment arbitral awards, have undergone changes of various kinds, most of them in terms of achieving a greater balance between the protection of investments and the protection of the regulatory powers of States, in accordance with the theory of proportionality. Important arbitral awards have recently been issued, which have had as its central theme the protection of public health. COVID-19 cases will further drive these changes. This article aims to provide some elements of analysis that may allow investors and Host States to know what can be expected in terms of investment arbitration and public health, in extraordinary times of international health crisis.